2017
DOI: 10.3390/medsci5020007
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbations in COPD Patients with Bronchiectasis

Abstract: There is evidence that coexisting bronchiectasis (BE) in patients with chronic obstructive pulmonary disease (COPD) aggravates the course of the disease. In this study, we aimed to evaluate the frequency and severity of bacterial exacerbations in COPD patients with BE. The frequency and duration of bacterial exacerbations treated in a 12-month period, as well as the duration of the exacerbation-free interval, were evaluated in 54 patients with COPD (Group D) who were diagnosed and assessed according to officia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 31 publications
0
20
1
1
Order By: Relevance
“…Minov et al identified a shorter duration of exacerbation‐free interval (expressed in days) in patients with COPD and associated bronchiectasis than patients with COPD without BE (ranging from 37‐82 days vs 49‐88 days, P = 0.0149) …”
Section: Comorbiditiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Minov et al identified a shorter duration of exacerbation‐free interval (expressed in days) in patients with COPD and associated bronchiectasis than patients with COPD without BE (ranging from 37‐82 days vs 49‐88 days, P = 0.0149) …”
Section: Comorbiditiesmentioning
confidence: 99%
“…The eosinophil count is a marker for eosinophilic airway inflammation and a predictive biomarker for the efficacy of ICS treatment in patients with COPD exacerbations . COPD patients with eosinophilia (≥2%) have an increased risk of AECOPD . The first study to investigate the prevalence of blood eosinophilia (defined as ≥300 cells/L) among inpatients with AECOPD evidenced a higher frequency of exacerbations during the 1‐year follow‐up period compared to patients without eosinophilia .…”
Section: Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations